Cognitive and graded activity training can alleviate persistent fatigue after stroke: a randomized, controlled trial - Zedlitz, Aglaia M E E; Rietveld, Toni C M; Geurts, Alexander C; Fasotti, Luciano (Stroke (1970), 2012)
Fatigue is a common, persistent consequence of stroke, and no evidence-based treatments are currently available to alleviate fatigue. A new treatment combining cognitive therapy (CO) with graded activity training (GRAT), called COGRAT, was developed to alleviate fatigue and fatigue-related symptoms. This study compared the effectiveness of the COGRAT intervention with a CO-only intervention after a 3-month qualification period without intervention. This randomized, controlled, assessor-blind clinical trial was conducted in 8 rehabilitation centers. Eighty-three stroke patients (>4 months after stroke) were randomly assigned to 12 weeks of CO or COGRAT after qualification. Seventy-three patients completed treatment and 68 were available at follow-up. Primary outcomes (Checklist Individual Strength-subscale Fatigue (CIS-f); self-observation list-fatigue (SOL-f)) and secondary outcomes (Hospital Anxiety and Depression Scale, Stroke-Adapted Sickness Impact Profile, SOL-pain, SOL-sleep-D, 6-minute walk test) were collected at baseline (before and after qualification period) and after treatment (immediate and 6-month follow-up). The qualification period showed stable outcome measures. Both treatments showed significant beneficial effects on fatigue (CIS-f: η(p)(2)=0.48, P<0.001) and other outcomes (except pain and anxiety) with intention-to-treat analyses. Gains for the COGRAT group exceeded those in the CO group on number of individuals showing clinical improvement on the CIS-f (≥8 points: 58% versus 24%) and on physical endurance (η(p)(2)=0.20, P<0.001). A 12-week cognitive therapy program can alleviate persistent fatigue after stroke. The best results are obtained when cognitive therapy is augmented with graded activity training. Clinical Trial Registration- URL: http://www.trialregister.nl. Unique identifier: NTR2704.